Desenvolvimento profissional docente e a pós-graduação stricto sensu: reverberações, trajetórias e resistências na Educação Básica - Santos, Tuany Cristina Carvalho (Universidade Estadual de Ponta Grossa (UEPG), 2026)
Teacher professional development (TPD), the object of study of this research, is understood as a relational process produced through the interaction between educational trajectories, embodied dispositions (habitus), accumulated forms of capital, and the positions occupied by teachers within the educational and academic fields, under specific structural and political conditions. Therefore, it is intertwined with teacher education and life trajectories, although it also depends on adequate and fair working conditions. The research problem is thus formulated as follows: How does stricto sensu graduate education in Education reverberate in the professional development of Basic Education teachers who are graduates of this stage of education? The general objective is to understand how stricto sensu graduate education in Education reverberates in the professional development of Basic Education teachers who have completed this stage of education. The specific objectives are: (a) to identify aspects of the socio-historical trajectories of Basic Education teachers, graduates of stricto sensu graduate programs in Education, that impact their professional development; and (b) to unveil possibilities and limitations in the professional development of Basic Education teachers stemming from stricto sensu graduate education. The thesis defended is that stricto sensu graduate education in Education constitutes a relevant space for expanding the professional development of Basic Education teachers, as it fosters the incorporation of investigative dispositions, the expansion of cultural and scientific capital, and the constitution of the teacherresearcher. However, the reverberations of this educational experience do not occur in a linear or automatic manner, as they are conditioned by the socio-historical trajectories of teachers and by the structures of the academic and school fields. Thus, teacher professional development is configured as a relational process resulting from the interaction between trajectories, forms of capital, and structural conditions that enable and/or constrain the mobilization of knowledge produced in graduate education within the school context. The theoretical-epistemological framework is grounded in the praxiology of Pierre Bourdieu (1996, 2003, 2004, 2009a). This is a qualitative research study of an explanatory and analytical nature, conducted with graduates of the Graduate Program in Education at the State University of Ponta Grossa who work in Basic Education after completing their degrees. Data production occurred in three stages: questionnaires answered by 67 graduates, (auto)biographical letters written by 12 participants, and a discussion group with 9 teachers. Data were analyzed based on Bourdieu’s methodological levels (2022) through thematic analysis (Braun; Clarke, 2006). The results indicate that stricto sensu graduate education has been increasingly occupied by Basic Education teachers, constituting a relevant space for continuing education. The formative experience contributes to expanding teachers’ cultural and scientific capital, strengthening investigative dispositions, and re-signifying their relationship with knowledge and pedagogical practice. However, the data also reveal that such reverberations largely occur at an individual level, due to limitations related to working conditions, professional recognition, and weaknesses in the articulation between university and school. In this context, it is observed that, although this form of education expands possibilities for reflection and professional practice, its contributions are mediated by teachers’ social trajectories and by the institutional conditions that shape the educational and academic fields.
Keywords: desenvolvimento profissional docente; formação continuada de professores; pós-graduação stricto sensu; educação básica; teacher professional development; continuing teacher education; stricto sensu graduate education; basic education